The miniature pig as an animal model in biomedical research - Vodicka, Petr; Smetana, Karel; Dvoránková, Barbora; Emerick, Teresa; Xu, Yingzhi Z; Ourednik, Jitka; Ourednik, Václav; Motlík, Jan (Annals of the New York Academy of Sciences, 2005)
Crucial prerequisites for the development of safe preclinical protocols in biomedical research are suitable animal models that would allow for human-related validation of valuable research information gathered from experimentation with lower mammals. In this sense, the miniature pig, sharing many physiological similarities with humans, offers several breeding and handling advantages (when compared to non-human primates), making it an optimal species for preclinical experimentation. The present review offers several examples taken from current research in the hope of convincing the reader that the porcine animal model has gained massively in importance in biomedical research during the last few years. The adduced examples are taken from the following fields of investigation: (a) the physiology of reproduction, where pig oocytes are being used to study chromosomal abnormalities (aneuploidy) in the adult human oocyte; (b) the generation of suitable organs for xenotransplantation using transgene expression in pig tissues; (c) the skin physiology and the treatment of skin defects using cell therapy-based approaches that take advantage of similarities between pig and human epidermis; and (d) neurotransplantation using porcine neural stem cells grafted into inbred miniature pigs as an alternative model to non-human primates xenografted with human cells.
Keywords: Disease Models, Animal; modely nemocí na zvířatech; oocyty; lidé; Aneuploidy; aneuploidie; Humans; prasata; kmenové buňky; epidermální buňky; Neurodegenerative Diseases; Biomedical Research; Animals; geneticky modifikovaná zvířata; zvířata; biomedicínský výzkum; neurony; Stem Cells; Oocytes; Swine; Epidermal Cells; Neurons; Animals, Genetically Modified; neurodegenerativní nemoci